Characterization of VuMATE1 Expression in Response to Iron Nutrition and Aluminum Stress Reveals Adaptation of Rice Bean (Vigna umbellata) to Acid Soils through Cis Regulation - Liu, Meiya; Xu, Jiameng; Lou, Heqiang; Fan, Wei; Yang, Jianli; Zheng, Shaojian (Frontiers in Plant Science, 2016)
Rice bean (Vigna umbellata) VuMATE1 appears to be constitutively expressed at vascular system but root apex, and Al stress extends its expression to root apex. Whether VuMATE1 participates in both Al tolerance and Fe nutrition, and how VuMATE1 expression is regulated is of great interest. In this study, the role of VuMATE1 in Fe nutrition was characterized through in planta complementation assays. The transcriptional regulation of VuMATE1 was investigated through promoter analysis and promoter-GUS reporter assays. The results showed that the expression of VuMATE1 was regulated by Al stress but not Fe status. Complementation of frd3-1 with VuMATE1 under VuMATE1 promoter could not restore phenotype, but restored with 35SCaMV promoter. Immunostaining of VuMATE1 revealed abnormal localization of VuMATE1 in vasculature. In planta GUS reporter assay identified Al-responsive cis-acting elements resided between -1228 and -574 bp. Promoter analysis revealed several cis-acting elements, but transcription is not simply regulated by one of these elements. We demonstrated that cis regulation of VuMATE1 expression is involved in Al tolerance mechanism, while not involved in Fe nutrition. These results reveal the evolution of VuMATE1 expression for better adaptation of rice bean to acid soils where Al stress imposed but Fe deficiency pressure released.